1967
DOI: 10.1111/j.1365-2494.1967.tb00514.x
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation in Appearance and Growth of Grass Roots

Abstract: Data from two field experiments, and from a root observation trench, suggest an annual cycle of root growth by grass swards. The production of adventitious roots from the tillers of four grass species, and from perennial ryegrass in a grass/clover sward varied greatly during the year. They were produced in increasing numbers through late winter to early spring; this rate fell sharply in April or May, and was low in summer. The differences in this annual cycle between grass species were small. Examination of ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
35
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(40 citation statements)
references
References 9 publications
(14 reference statements)
5
35
0
Order By: Relevance
“…The estimates of ryegrass root longevity were similar to those reported by Garwood (1967) in the United Kingdom, although the estimates made by Troughton (1981) were slightly larger than those reported here. Garwood (1967) showed that ryegrass root longevity (as determined by the period which elapsed before the root cortex became brown when observed in a field rhizotron) varied between 61 and 188 days.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The estimates of ryegrass root longevity were similar to those reported by Garwood (1967) in the United Kingdom, although the estimates made by Troughton (1981) were slightly larger than those reported here. Garwood (1967) showed that ryegrass root longevity (as determined by the period which elapsed before the root cortex became brown when observed in a field rhizotron) varied between 61 and 188 days.…”
Section: Discussionsupporting
confidence: 83%
“…Garwood (1967) showed that ryegrass root longevity (as determined by the period which elapsed before the root cortex became brown when observed in a field rhizotron) varied between 61 and 188 days. Root longevity was greatest when the roots were produced in the autumn and winter, and least when the roots were produced in spring or summer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this soil, virtually all 1994) or in below-ground production, because of the the soil C was derived from C4 photosynthesis and very short lifespan of many roots. That roots can be so had a very low S^^C signal ( 21 %"); they were short-lived has been known for many years able to detect recently added C because it had been (Garwood, 1967), but only with the advent of fixed by C3 photosynthesis (i^^^C t\'pically -28%o).…”
Section: Introductionmentioning
confidence: 99%
“…Historic studies of grass sward dynamics have tended to focus separately on behavior of leaves [1,2], tiller populations [3], or roots [4]. Compartmentalisation of sward dynamics studies in this way probably occurred, in part, as a pragmatic reaction to the fact that such studies are extremely time consuming, and focusing on one aspect of sward behavior helps ensure data quality.…”
Section: Introductionmentioning
confidence: 99%